Hydatid cyst: Introducing a new surgical approach towards hepato-pulmonary fistula, a case report. (April 2022) - Khalifeh, Yara; El Hadi, Dalia; Nassar, Hussein; El Hout, Walid; Faraj, Walid; Khalife, Mohammad
Abstract: Introduction and importance: Hydatid disease, caused by the zoonotic parasite Echinococcus granulosus, presents as cysts most commonly in the liver and the lungs. A hepato-pleural fistula is considered one of its complications and surgery remains the mainstay of treatment. A simultaneous invasive thoracic and abdominal access is routinely needed which is accompanied by increased morbidity and mortality. Case presentation: In this case report, we present an innovative, less invasive, non-classical approach. Clinical discussion: We introduce a successful transabdominal transdiaphragmatic laparoscopic technique for the management of a hepato-pulmonary fistula secondary to hydatid disease of the liver. Conclusion: Compared to the classical method, this new surgical approach towards hepato-pulmonary fistula paves the way for minimally invasive surgeries to manage complicated hydatid disease with a lower mortality and morbidity, faster recovery and shorter hospital stay. The work has been reported in line with the SCARE 2020 criteria. Highlights: Hydatid disease caused by Echinococcus granulosus presents as cysts most commonly in the liver and lungs. Hepato-pleural fistula is considered one of the reported complications. Surgery is the mainstay of treatment, traditionally done through a trans-thoracic approach with an abdominal access. Such surgeries have high morbidity & mortality especially in developing countries that have modest expertise in this field. We report successful transabdominal transdiaphragmatic laparoscopic surgery of liver hydatid cyst with hepatopleural fistula.